2013
DOI: 10.1371/journal.pone.0074451
|View full text |Cite|
|
Sign up to set email alerts
|

Aureochrome 1a Is Involved in the Photoacclimation of the Diatom Phaeodactylum tricornutum

Abstract: Aureochromes constitute a family of blue light (BL) receptors which are found exclusively in heterokont algae such as diatoms (Bacillariophyceae) and yellow-green algae (Xanthophyceae). Previous studies on the diatom Phaeodactylum tricornutum indicate that the formation of a high light acclimated phenotype is mediated by the absorption of BL and that aureochromes might play an important role in this process. P. tricornutum possesses four genes encoding aureochromes. In this study we confirm the nuclear localis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 65 publications
3
75
1
Order By: Relevance
“…While blue is the wavelength with the highest level of energy and red with a lowest, both are harvested by pigments fuelling the photosynthetic machinery and are sensed by photoreceptors (Depauw et al ., ) inducing downstream cascades of metabolic and physiological reactions (Depauw et al ., ; Schellenberger Costa et al ., ; Brunet et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…While blue is the wavelength with the highest level of energy and red with a lowest, both are harvested by pigments fuelling the photosynthetic machinery and are sensed by photoreceptors (Depauw et al ., ) inducing downstream cascades of metabolic and physiological reactions (Depauw et al ., ; Schellenberger Costa et al ., ; Brunet et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Schellenberger Costa et al (35) suggested that aureochrome 1a is involved in photoacclimination. Furthermore, Huysman et al (36) reported that it mediates induction of diatom-specific cyclin dsCYC2 and controls the onset of cell division, and suggested that it functions synergistically with the bZIP transcription factor bZIP10 to induce dsCYC2 transcription.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the expression of silicon transporters is up‐regulated during silicon starvation in diatoms (Hildebrand et al ., 1998), and genes in the photorespiratory pathway are up‐regulated during increased glycolate production (Parker et al ., 2004). Genes such as LHCX1 and AUREOCHROME 1‐a in Phaeodactylum tricornutum are known to be light‐responsive (Bailleul et al ., 2010; Costa et al ., 2013). In the case of AUREOCHROME 1‐a, the specific mechanism by which light regulates cell division through the activity of dsCYC2 (a diatom‐specific cyclin) has been elucidated (Huysman et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%